2021
DOI: 10.1111/jocn.15724
|View full text |Cite
|
Sign up to set email alerts
|

What's going on after hospital? – Exploring the transition from hospital to home and patient experiences of nurse‐led follow‐up phone calls

Abstract: Aims and Objectives To explore the transition from hospital to home and patient experiences of nurse‐led post‐operative follow‐up phone calls after thoracic surgery. Background Enhanced Recovery After Surgery protocol places new demands on patients after hospital. Need for a proactive approach to improve the post‐operative follow‐up process in the home is required. Design Qualitative intervention study. Methods Interviews were conducted with patients who had received a post‐operative phone call after hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“… 51 52 55 56 58 59 They complained that it was difficult to obtain healthcare professionals’ treatments after discharge, and therefore, they felt vulnerable: ‘There was no rehab in the hospital this time, you were just shunted out the door after four days, and so obviously that was cost-cutting.’ 56 This disconnection was regarded by patients as the main barrier to self-care at home: ‘Because I feel that after having such major surgery you need all the care and attention you can get from well trained staff that are there as a back up when you need them.’ 31 Although nearly all patients experienced nutritional problems (such as weight loss), only a few were able to receive guidance at home from clinical dietitians. 31 48 51 52 Furthermore, patients said they would be grateful if healthcare professionals would call at different stages of their recovery at home: ‘…It would have been good to get another one [phone call] at a later stage when I was feeling more on top of things…’ 47 …”
Section: Resultsmentioning
confidence: 99%
“… 51 52 55 56 58 59 They complained that it was difficult to obtain healthcare professionals’ treatments after discharge, and therefore, they felt vulnerable: ‘There was no rehab in the hospital this time, you were just shunted out the door after four days, and so obviously that was cost-cutting.’ 56 This disconnection was regarded by patients as the main barrier to self-care at home: ‘Because I feel that after having such major surgery you need all the care and attention you can get from well trained staff that are there as a back up when you need them.’ 31 Although nearly all patients experienced nutritional problems (such as weight loss), only a few were able to receive guidance at home from clinical dietitians. 31 48 51 52 Furthermore, patients said they would be grateful if healthcare professionals would call at different stages of their recovery at home: ‘…It would have been good to get another one [phone call] at a later stage when I was feeling more on top of things…’ 47 …”
Section: Resultsmentioning
confidence: 99%
“…Receiving such a call would have reduced their fear of being thought bothersome. Donsel et al 23 highlighted the importance of having a nurse call the patient during postoperative follow-up instead of the patients having to initiate the call. When the patients were contacted, they were able to avoid feeling like they were disturbing the healthcare team, which was seen to be the case if the patient needed to initiate the contact.…”
Section: Discussionmentioning
confidence: 99%
“…Together with some other reasons, feeling lonely may occur due to isolation during periods of disability. 27 Donsel et al 23 suggested that a phone call from a nurse sometime after discharge could reduce those feelings. The participants emphasized that next of kin could play an important role in the recovery process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-discharge surveillance is an important part of the pathway, as patients may have additional care needs once home [ 108 ]. A survey indicated that the post-discharge telephone checkup was valued most highly out of all ERAS components postoperatively [ 109 ], follow-up calls aided in answering unexpected questions patients had post discharge (despite prior attempts to optimize knowledge) [ 110 ] and relieving the isolation faced by patients ‘left alone with their illness’ [ 111 ]. Active post-discharge surveillance programs are cost-effective, as postoperative issues may be resolved in the outpatient setting thereby reducing readmission or emergency department presentation [ 112 ].…”
Section: Components Of Erpsmentioning
confidence: 99%